2021
DOI: 10.3390/cancers13081754
|View full text |Cite
|
Sign up to set email alerts
|

The “COVID-19 Pandemic Gap” and Its Influence on Oncologic Outcomes of Bladder Cancer

Abstract: Coronavirus-19 (COVID-19)-induced effects on deferred diagnosis and treatment of bladder cancer (BC) patients are currently not clarified. The aim of this study was to evaluate outcomes of the COVID-19 pandemic by considering its effects on tumor stage and grade, and to create feasible clinical triage decisions. A retrospective single-center analysis of all patients who underwent diagnostic and surgical procedures due to BC, during January 2019 and December 2020, was performed. Due to COVID-19 lockdowns, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…However, several consequences might arise from the observed decrease in the number of urologic oncology surgical and diagnostic procedures performed during the COVID-19 pandemic. Recent research works demonstrated how a decrease in diagnosis and a delay in surgical treatment of early tumors might lead to cancer upstaging and worse patients’ prognosis [ 14 , 22 , 23 , 33 , 34 , 39 ]. Moreover, the reduction in surgeries for localized disease might lead to subsequent higher surgical complexity, with greater risk of complications, and lower possibility of training for residents and young surgeons [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several consequences might arise from the observed decrease in the number of urologic oncology surgical and diagnostic procedures performed during the COVID-19 pandemic. Recent research works demonstrated how a decrease in diagnosis and a delay in surgical treatment of early tumors might lead to cancer upstaging and worse patients’ prognosis [ 14 , 22 , 23 , 33 , 34 , 39 ]. Moreover, the reduction in surgeries for localized disease might lead to subsequent higher surgical complexity, with greater risk of complications, and lower possibility of training for residents and young surgeons [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the urology team of our institution has described a reduction in all urologic activities performed during the first COVID-19 wave in the three largest public hospitals in Lombardy (Brescia, Bergamo and Milan) [ 12 ]. In accordance with recommendations by international urological societies, some urologic oncology surgical procedures have undergone a significant reduction in volume based on specific prioritization strategies, leading to an increased backlog of cases and possibly a worse prognosis for some patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study provides real-world evidence of TGCT stage migration associated with the COVID-19 pandemic. A few others have demonstrated stage migration in other cancer types, but these have been limited to single-centre institutions; 36 38 the present study provides a population-level assessment of stage migration. Most modelling studies have focused on more common cancer types to characterize the greatest impacts of the pandemic on health care systems.…”
Section: Discussionmentioning
confidence: 91%
“…Predictably, patients often develop not only the fear of being affected by malignant lesions but also of exposing themselves to the risk of infection by attending hospitals or doctors’ surgeries. Moreover, the revised day-to-day management of patients and the risk of infection by SARS-CoV-2 requires that fewer patients are seen by medical staff ( Campisi et al, 2020 ; Jacob et al, 2021 ; Ruiz-Medina et al, 2021 ; Tulchiner et al, 2021 ; Popovic et al, 2022 ; Zubair et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%